Cutting a Long Intron Short: Recursive Splicing and Its Implications - Georgomanolis, Theodore; Sofiadis, Konstantinos; Papantonis, Argyris (Frontiers in Physiology, 2016)
Over time eukaryotic genomes have evolved to host genes carrying multiple exons separated by increasingly larger intronic, mostly non-protein-coding, sequences. Initially, little attention was paid to these intronic sequences, as they were considered not to contain regulatory information. However, advances in molecular biology, sequencing, and computational tools uncovered that numerous segments within these genomic elements do contribute to the regulation of gene expression. Introns are differentially removed in a cell type-specific manner to produce a range of alternatively-spliced transcripts, and many span tens to hundreds of kilobases. Recent work in human and fruitfly tissues revealed that long introns are extensively processed cotranscriptionally and in a stepwise manner, before their two flanking exons are spliced together. This process, called “recursive splicing”, often involves non-canonical splicing elements positioned deep within introns, and different mechanisms for its deployment have been proposed. Still, the very existence and widespread nature of recursive splicing offers a new regulatory layer in the transcript maturation pathway, which may also have implications in human disease.